Scoring balloon predilation before bioresorbable vascular scaffold implantation in patients with in-stent restenosis: the RIBS VI 'scoring' study. Issue 2 (16th June 2020) - Alfonso, Fernando; Cuesta, Javier; García del Blanco, Bruno; Bosa, Francisco; Pérez de Prado, Armando; Masotti, Mónica; Trillo, Ramiro; Rumoroso, José Ramón; Moreno, Raul; Cequier, Angel; Gutiérrez, Hipólito; García Touchard, Arturo; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Currently drug-eluting stents (DES) and drug-eluting balloons are recommended in patients with in-stent restenosis (ISR). However, the efficacy of bioresorbable vascular scaffolds (BVS) after scoring balloon (SCB) predilation in these patients is unknown. Methods: RIBS VI (NCT02672878) and RIBS VI 'Scoring' (NCT03069066) are prospective multicentre studies assessing the value of BVS in patients with ISR. Inclusion and exclusion criteria were identical in both studies. Results of conventional BVS implantation (112 patients) were compared with those obtained with systematic SCB therapy before BVS (108 patients). Angiographic follow-up was scheduled for all patients. Results: On late angiography (93% of eligible patients) the in-segment minimal lumen diameter (primary end-point) (1.88 ± 0.5 vs. 1.90 ± 0.4 mm, P = 0.81), % diameter stenosis (28 ± 17 vs. 29 ± 15%), late lumen loss (0.23 ± 0.4 vs. 0.22 ± 0.4 mm) and binary restenosis rate (8.5 vs. 9.3%) were similar in the conventional BVS and SCB + BVS groups, respectively. At 1-year follow-up (100% of patients) target lesion revascularization (TLR) requirement (9.8 vs. 11.1%) was similar with the two strategies. Freedom from cardiac death, myocardial infarction and TLR was 88% and 87%, respectively. Results remained unchanged after adjusting for potential baseline confounders and were consistent in 10 prespecified subgroups. Conclusion: This study suggests that results of conventional BVS implantation in patients with ISR are not improved by systematic predilation with SCB. ClinicalTrials.gov ID: NCT02672878 (RIBS VI) and NCT03069066 (RIBS VI 'Scoring').